Estudio ergonómico y propuesta de plan de mejora para los trabajadores de la Fundación General Ecuatoriana, en el periodo noviembre 2014 a julio 2015 - Uribe Zurita, Andrea Isabel (2016)
The following thesis work presents an alternative qualification to improve the physical comfort of the workplace of employees of the General Ecuadorian Foundation. Initially emerging needs were identified through a survey of middle and senior management to accomplish this is to identify needs looking comply with safety regulations and occupational health. The study was conducted in compliance with the provisions of the 2393 Decree, and the Andean Instrument on Safety and health Decision 584, Resolution 957. Finally, the results can be implemented methods in order to improve compliance with the activities of workers in the Ecuadorian General Foundation as improved work spaces, installation of signage and other factors getting more physical and environmental comfort optimal starting from the ideal conditions of safety and health in those spaces